Association between leisure-time physical inactivity and hospital care in adult in the city of Salvador-Brasil - Francisco José Gondim Pitanga; Ines Lessa (Universidade Federal de Santa Catarina, 2008)
Hospital inpatient care is a significant source of expense for the healthcare system. In this study the objectivewas to verify the existence of an association between physical inactivity during free time (IFTL) and IHTC (hospital admissionsfor whatever cause), due to cardiac problems (IHPC) and diabetes (IHD) in adults in the city of Salvador in Brazil. Thiswas a cross-sectional study of a sample of 2290 adults ≥ 20 years of age, 1021 (44.6%) being men. Subjects were definedas IFTL if they stated that they did not take part in physical activity during leisure time, while hospital admissions wereself-reported. Logistic regression analysis was used to estimate the odds ratio (OR) between IFTL, IHTC, IHPC and IHDto a confidence interval of 95%. Multivariate analysis was then applied and detected an association between IFTL, IHTC,IHPC and IHD in men, while among the women there was only an association between IFTL and IHD. The results of thisstudy are of importance for public health, to the extent that they could be used to facilitate the management of programs toencourage participation in physical activities with a view to preventing hospital admissions and consequently to reducingthe costs to the health system.